PENGARUH GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN CSR SEBAGAI VARIABEL MODERASI - Yohana, Yohana Mutiara Minsi; Fery Citra Febriyanto (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This study aims to determine the effect of good corporate governance and financial performance on firm value, with CSR as a moderating variable, in state-owned enterprises (BUMN) for the period 2019-2022. This research is quantitative, using secondary data obtained from the Indonesia Stock Exchange (IDX) and the respective company websites. The analytical techniques used in the study include multiple linear regression and moderated regression analysis (MRA) with the help of Eviews version 12 software. The study was conducted on state-owned enterprises (BUMN). The data sampling technique employed was purposive sampling, with a sample of 15 companies observed over 4 years (2019-2022). The results of this study indicate that partially, good corporate governance influences firm value, while financial performance does not affect firm value. CSR does not moderate the effect of good corporate governance and financial performance on firm value.